The MVA-VP2-NS1-2A-NS2-Nt vaccine candidate provides heterologous protection in sheep against bluetongue virus - Jiménez-Cabello, Luis; Utrilla-Trigo, Sergio; Illescas-Amo, Miguel; Rodríguez-Sabando, Karen; Benavides-Silván, Julio; Calvo-Pinilla, Eva; Ortego, Javier (Frontiers in Immunology, 2025)
Bluetongue (BT) is an important arthropod-borne livestock disease transmitted by Culicoides midges. The etiological agent, Bluetongue virus (BTV), can lead to severe economic losses due to reduced productivity and trade restrictions. Nowadays, classical vaccines based on inactivated viruses are used to control outbreaks but do not confer multiserotype protection, which reinforces the idea of pursuing research into developing strategies that enhance the immune response directed to conserved antigenic regions, aiming broader protection across multiple serotypes. Recently, we described a vaccine candidate that confers full protection against a homologous serotype of BTV based on recombinant Modified Vaccinia Virus Ankara (MVA) co-expressing the highly conserved BTV nonstructural protein NS1 and the N-terminal end of NS2 along with protein VP2 of BTV-4. In this work, we evaluated the multiserotype protective capacity of this recombinant vaccine candidate in sheep after infection with the heterologous virus BTV-8, achieving a significant blockade of viral replication and attenuation of the clinical signs induced by BTV. After infection, vaccinated animals showed more regulated pro-inflammatory cytokine levels compared to non-vaccinated sheep. In addition, we noticed the induction of potent T cell immune responses specific to NS1 and NS2-Nt proteins of BTV, mainly based on CD8+ T cells, which could mediate the protection against BTV-8. Moreover, stimulated immunized sheep PBMCs with BTV antigens triggered the secretion of IL-6, IL-1β, IL-1α, IL-17a, IL-10 and IFN-γ, cytokines that play crucial roles in initiating immune responses.